Informal Institutions in Autocracies: Analytical Perspectives and the Case of the Chinese Communist Party - Patrick Köllner (German Institute of Global and Area Studies (GIGA), 2013)
Analyses of the shape and functioning of systems of political rule need to address informal institutions, which exist alongside and can relate to formal institutions in various ways. In this paper, I first discuss some analytical foundations of the study of such institutions. I then suggest that a focus on political regimes - understood as the configuration of formal and informal institutions shaping and reflecting the access to and the exercise of political power - can be particularly useful for analysing the shape and functioning of autocracies. Finally, I use such a regime focus to study the Chinese Communist Party and its leadership succession process, which is characterised by increasing institutionalisation and complementary as well as substitutive relations between formal and informal institutions.
Keywords: 300; informal institutions; political regimes; autocracies; Chinese Communist Party; political succession